Effect of Work-Family Conflict and Job Satisfaction on Quality of Work Life - Owolabi, Ademola Benjamin (Advances in Social Sciences Research Journal, 2015)
This study attempted to investigate the effect of work-family conflict and job satisfaction on quality of work life. Data were obtained from two hundred (200) respondents in which one hundred and eighty-nine was found valid for analysis. The respondent used consists of (100) female workers and (89) male workers both in the public and private sectors, respondents reside and work in Ado-Ekiti. Three instruments were used in this study to measure work-family conflict, job satisfaction and quality of work life. Three hypotheses were tested. This study shows that there is a significant effect of work-family conflict and job satisfaction on quality of work life, but there are no significant sex differences in work-family conflict, job satisfaction and quality of work life.